Tobacco Use Among Individuals With Intellectual or Developmental Disabilities: A Brief Review - Steinberg, Marc L. (Intellect Dev Disabil, 2009)
Tobacco use is the leading preventable cause of death in the United States. Although few tobacco control efforts target individuals with intellectual and/or developmental disabilities, this population may be especially vulnerable to the deleterious effects of tobacco use and dependence. Individuals with intellectual and developmental disabilities suffer from the health, financial, and stigmatizing effects of tobacco use. The present review examined the current literature with respect to the prevalence and patterns of tobacco use in individuals with intellectual and developmental disabilities, the importance of addressing tobacco use in these smokers, and policies surrounding tobacco use in this population. Suggestions for additional avenues of inquiry as well as modifications to current cessation treatments are proposed.